Indigenous elements in Tibetan tantric religion - Mayer, R (Stanislav Juhaňák – TRITON, 2014)
This paper is an attempt at an overview of the still only partially understood topic of indigenous elements within Tibetan tantric religion, with particular focus on the underlying historical and cultural dynamics. Drawing on the research Cathy Cantwell and I have done together in recent years, and above all greatly indebted to the discoveries of many other scholars, it was inspired by the need to communicate the topic to non-specialist academic colleagues, on the one hand avoiding excessive technical obscurantism, but on the other hand utilising up to date research.